2021
DOI: 10.3390/biom11081231
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Cancer Glucose Metabolism: At the Bench or at the Bedside?

Abstract: Several studies reported that metformin, the most widely used drug for type 2 diabetes, might affect cancer aggressiveness. The biguanide seems to directly impair cancer energy asset, with the consequent phosphorylation of AMP-activated protein kinase (AMPK) inhibiting cell proliferation and tumor growth. This action is most often attributed to a well-documented blockage of oxidative phosphorylation (OXPHOS) caused by a direct interference of metformin on Complex I function. Nevertheless, several other pleiotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…AMPK, an intracellular energy sensor and controller, has been originally served as a therapeutic target for the treatment of diabetes [ 30 ]. However, the regulation of AMPK signaling has also been further reported to potentiate the cytotoxicity and efficacy of anticancer drugs in treating patients with different types of cancers [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK, an intracellular energy sensor and controller, has been originally served as a therapeutic target for the treatment of diabetes [ 30 ]. However, the regulation of AMPK signaling has also been further reported to potentiate the cytotoxicity and efficacy of anticancer drugs in treating patients with different types of cancers [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the regulation of AMPK signaling has also been further reported to potentiate the cytotoxicity and efficacy of anticancer drugs in treating patients with different types of cancers [ 31 , 32 ]. Moreover, this is also because of its energy homeostasis regulatory mechanism [ 30 ]. It has been shown that (i) AMPK activation by adding the AICAR, an agonist, significantly increasing the efficacious treatment for lethal breast cancer [ 31 , 32 ]; (ii) AMPK activation could promote the mitochondrial activity to increase the treating sensitivity in patients with myeloid leukemia [ 33 ]; (iii) AICAR activates the AMPK signaling to enhance the anticancer effect of chemotherapeutic agents in prostate cancer cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is able to directly and indirectly interact with many enzymes, such as mitochondrial electron transport chain (ETC) complex I, adenosine 5′-monophosphate-activated protein kinase (AMPK), glycerol 3-phosphate dehydrogenase, fructose 1-6-bisphosphatase, and glucose 6P-phosphatase, which highlights the metabolic properties of metformin [ 15 , 35 , 36 , 37 , 38 , 39 , 40 ]. Metformin’s influence on multiple metabolic pathways is produced by targeting ETC complex I, the inhibition of which leads to subsequent AMPK activation [ 41 , 42 , 43 ].…”
Section: Multifactorial Actions Of Metforminmentioning
confidence: 99%
“…PPP may be a critical pathway in lipogenesis. In a recent study on cancer cells, metformin was reported to interfere with several enzymes related to PPP and decreased the effect of PPP via modulation of mTORC (74). However, the information about the association between metformin and 6PGD remains unclear (74).…”
Section: Nafld For 6 Monthsmentioning
confidence: 99%
“…In a recent study on cancer cells, metformin was reported to interfere with several enzymes related to PPP and decreased the effect of PPP via modulation of mTORC (74). However, the information about the association between metformin and 6PGD remains unclear (74). Briefly, in vitro, in vivo, or clinical trials have provided evidence that AMPK activation may be a critical step in improving lipid metabolism.…”
Section: Nafld For 6 Monthsmentioning
confidence: 99%